A retrospective comparison of microwave ablation and high intensity focused ultrasound for treating symptomatic uterine fibroids. Issue 3 (March 2015) - Zhao, Wen-Peng; Han, Zhi-Yu; Zhang, Jing; Liang, Ping
Highlights: Both HIFU and PMWA are thermal ablation techniques and they all provide safe and reliable alternative treatment methods for uterine fibroids. However, whether there are obvious difference between these two kinds of approaches in improving symptom, treatment time, ablation rate, regression rate and adverse events, until now, there are no clinical trials which have been performed to compare the therapeutic effects of HIFU and PMWA. In this research, we retrospectively compare the results of these two treatment methods. To our knowledge, our study is the first directly comparing long-term outcome after PMWA and HIFU in patients with uterine fibroids. Abstract: Objectives: To retrospectively compare the effectiveness and safety of percutaneous microwave ablation (PMWA) and ultrasound-guided high-intensity focused ultrasound (USgHIFU) for treating symptomatic uterine fibroids. Methods: Seventy-three women with symptomatic uterine fibroids who met the inclusion criteria were enrolled in our study from September 2012 to December 2013. Thirty-one patients with forty uterine fibroids underwent PMWA, and forty-two patients with fifty-one uterine fibroids underwent USgHIFU. A contrast-enhanced MRI was performed before and after treatment, and all patients were followed up for 6 months. Assessment endpoints included symptom severity scores (SSS), treatment time, ablation rate, fibroid regression rate and adverse events. Results: The mean age of the patients in our study was 35.4 ± 6.2 years (range, 21–49 years), and the median volume of uterine fibroids was 95.7 cm 3 (60.3–131.5 cm 3 ). The ablation rate of uterine fibroids was 79.8 ± 18.2% and 77.1 ± 14.9% in the PMWA group and the USgHIFU group, respectively, and showed no significant difference between the groups. Changes in SSS after PMWA were similar in the PMWA group (47.7 pre-treatment vs. 29.9 post-treatment) and USgHIFU group (42.1 pre-treatment vs. 24.6 post-treatment). The regression rate of uterine fibroids also showed no marked difference between the two groups (PMWA, 50.3%; USgHIFU, 52.4%). The median treatment time of the PMWA group was 46.2 min, which was demonstrably superior to USgHIFU. Finally, the occurrence rate of adverse events was the same in the two groups. Conclusions: The safety and effectiveness of PMWA and USgHIFU in the treatment of uterine fibroids were similar; however, the median treatment time of PMWA was shorter than that of USgHIFU.